Neuroendocrine Stress Response in Neonates with Kidney Diseases Against Asphyxia - A.M. Loboda; V.Ye. Markevich (Zaslavsky O.Yu., 2013)
Objective. To examine the neuroendocrine stress response on the basis of study of the dynamics of interleukin-1β (IL-1β) and cortisol in blood serum during the neonatal period in newborns with kidney diseases against asphyxia. Materials and Methods. The study involved 100 full-term infants with signs of kidney disease: 50 children who had severe asphyxia, and 50 children with moderate asphyxia. Comparison group included 20 children without asphyxia. The level of interleukin-1β and cortisol in blood serum were determined at 1-2, 7-8 and 25-30th days of life by ELISA technique. Results. In neonates with impaired renal function against asphyxia there were observed increase in IL-1β level in serum, enhancing of correlation between IL-1β and cortisol, which cause an increase in cortisol level. The highest content of serum cortisol observed at 1-2nd days of life (505.28 ± 36.96 nmol/l and 374.40 ± 11.36 nmol/l in children which suffered from severe and moderate asphyxia, respectively). Continuous stimulation of the adrenal cortex by cytokine in case of severe asphyxia leads to a change in the correlation's character (-0.328, p < 0.05) and inhibition of cortisol production by the end of the neonatal period.